Ultrasound Study of Trocar Site Hernia after Bariatric Surgery: Medium and Long-Term Follow-Up - Emilio López-Negrete Cueto; Aida Suárez Sánchez; Jose Luis Rodicio Miravalles; Sonia Amoza Pais; María Moreno Gijón; Sandra Sanz Navarro; Tamara Díaz Vico; Pablo Noriega Menéndez; Ana Montes García; Lourdes Sanz Álvarez (Journal of Abdominal Wall Surgery, 2025)
IntroductionPatients undergoing bariatric surgery have comorbidities and risk factors which favour incisional hernias. Bladeless trocars are safe and not very harmful, being the preferred choice without port closure. The objective of this study is to evaluate the true occurrence of trocar hernias (trocar site hernia) in these patients in medium and long term.Material and MethodsWe made an observational, descriptive, longitudinal, and retrospective study in patients who underwent bariatric surgery by laparoscopy with 12 mm bladeless trocars without fascial closure. We selected patients who agreed to participate in the study between January 2015 and July 2016. We also collected data on risk factors, pain scale, and ultrasound of port-site by an expert radiologist in 2018 and 2022.ResultsIn the first period 45 patients were included, with a mean age of 49.9 years and an initial BMI of 45.5 kg/m2. Most of them (88.9%) were operated by gastric bypass. Forty-five abdominal wall ultrasounds were performed in 2018 with findings of 7 trocar site hernia for a total of 185 explored ports (3.8%), all of them in the epigastric port (p < 0.001) and asymptomatic. In 2022, 32 ultrasound detected 7 trocar site hernia (4.4%), 3 new and 4 knowns, with 2 symptomatic patients at the trocar site hernia with mild symptoms not consulted.ConclusionThe incidence of trocar hernia in the medium and long term in postoperative bariatric surgery with 12 mm bladeless trocars without fascial closure is low, all of them being in the midline and paucity of symptoms. Our primary approach involves abstaining from closing the transmuscular accesses, deeming it unnecessary, while evaluating the closure or lateralization of the midline trocar.